Drivers and barriers to adoption of regenerative agriculture: cases studies on lessons learned from organic - Shawna Lemke; Nathan Smith; Christian Thiim; Katie Stump (International Journal of Agricultural Sustainability)
Regenerative agriculture has emerged as a potentially outcome-based paradigm centring on soil health, biodiversity and other environmental and social parameters. Early days of organic agriculture also focused on philosophy first and evolved into a process-based regulatory paradigm whose adoption remains small relative to conventional production. Five case studies of professional growers, representing a total of 100,000 acres of production, were collected to identify reasons for choosing to grow or stop growing organic, challenges faced and attitudes around regenerative agriculture. Growers identified issues of complex and unpredictable regulation, labour, inability to predict market trends and secure needed premiums, cost and effectiveness of natural fertilizers and lack of effectiveness in pest control. These growers adopted similar practices (e.g., integrated pest management) for environmental benefits across conventional and organic acres, and viewed consumer demand and potential profitability rather than environmental benefits as the main drivers for practising organic. Growers expressed interest in outcome-based regenerative agriculture. To be viable, a programme requires criteria on measurement and certification, regionally tailored flexibility and clear financial incentives. Growers doubt such a programme would replace organic but see opportunities for new marketing programmes, particularly in carbon sequestration and water management. Challenges identified by growers warrant further study.